농업용 신재생에너지 활용방안 연구 - 김연중 (한국농촌경제연구원, 2009)
The level of energy consumption in the agricultural and fisheries sector is small, accounting for about 1.2% of the nation's total energy consumption. However, energy consumption takes up a very large portion of business cost at the individual farmhouse level. The main purpose of this research is to review the possibilities of supplying energy-saving facilities under annual targets by 2020 and to present efficient ways to supply them by estimating annual government spending effects, CO2 reduction effects and cost-reduction effects at the farmhouse level. According to estimates, the supply and demand for geothermal heat pumps has been restricted even though the equipment is evaluated to have economic benefits. This is because the burden of initial investment is large and resulting effects are uncertain. In the case of timber pellets, it is hard to purchase them periodically and the price is high when compared with the thermal efficiency it provides. And then there is the difficulty of securing a storage area to stock up the voluminous pellets. Therefore, in order to promote the use of renewable energy, it is necessary to provide financial support to renewable energy facilities. Since the current tax-free petroleum policy for farms is available for a limited period of time, it is necessary to make careful follow-up measures. Particularly, it is essential to encourage the use of renewable energy in such facilities as large high-tech glasshouses. Also, specialized experts and construction companies should be fostered so that they can install specialized facilities that are suitable for different farming environment. Also, rules and relevant measures should be institutionalized to prevent shoddy construction by unqualified contractors. In order to save renewable energy, the government should continuously invest in research and development. Although renewable energy facilities are expensive currently, the possibility of expanding the demand for the facilities is very high since the supply price can be drastically lowered through continued research and development.